2020
DOI: 10.1186/s40008-020-0190-y
|View full text |Cite
|
Sign up to set email alerts
|

Estimating financing gaps in rice production in Southwestern Nigeria

Abstract: Rice is one of the most valuable cereal crops cultivated and consumed all over the world. It is a staple food in several African counties, Nigeria as an example and constitutes a large portion of the diet on a regular basis (Lu et al. 2018). Rice is cultivated in mostly all agro-ecological zones in Nigeria but on a relatively small scale. As asserted by FAO (2015), Nigeria is the continent's leading consumer of rice, one of the largest producers of rice in Africa and simultaneously one of the largest rice impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
22
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 35 publications
4
22
1
Order By: Relevance
“…This result is consistent with Ojo et al (2020) who found gender to have positive influence on profit inefficiency among smallholder rice farmers in Nigeria. However, Bahta and Baker found a negative relationship between gender and profit inefficiency.…”
Section: Determinants Of Profit Inefficiency Among Sheep Farmerssupporting
confidence: 91%
See 2 more Smart Citations
“…This result is consistent with Ojo et al (2020) who found gender to have positive influence on profit inefficiency among smallholder rice farmers in Nigeria. However, Bahta and Baker found a negative relationship between gender and profit inefficiency.…”
Section: Determinants Of Profit Inefficiency Among Sheep Farmerssupporting
confidence: 91%
“…Similar studies in Africa (e.g. Tijani et al 2006;Mawa et al 2014;Bahta and Baker, 2015;Ojo et al 2020) have analysed the profit efficiency of smallholder farmers. However, there is limited information available in South Africa on the profit efficiency of smallholder sheep farmers, thereby, making this study very relevant.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…It has become a staple food in Nigeria such that every household, both the rich and the poor, consumes a great quantity [14]. A combination of various factors seems to have triggered the structural increase in rice consumption over the years with consumption broadening across all socioeconomic classes, including the poor [15]. The rising demand could be as a result of increasing population growth and income level coupled with the ease of its preparation and storage [14].…”
Section: Introductionmentioning
confidence: 99%
“…It has become a staple food in Nigeria such that every household; both the rich and the poor consume a great quantity. A combination of various factors seems to have triggered the structural increase in rice consumption over the years with consumption broadening across all socio-economic classes, including the poor [23]. Rising demand could be as a result of increasing population growth and income level coupled with the ease of its preparation and storage.…”
Section: Introductionmentioning
confidence: 99%